Pengaruh Mata Kuliah Pengembangan Kepribadian Pancasila dalam Menyikapi Ilmu Pengetahuan dan Teknologi - Mursyidah Dwi Hartati; Ponohardjo; Mohamad Khamim (Universitas Pancasakti Tegal, 2018)
This research aimed to find out the effect of personality development subject in responding science and technology in responding science and technology. The population of the research was 103 students. Sampling technique used was proportionate cluster random sampling, in this case each class was taken 70% of students to be participant and it was 40 students. Data was questionnaire and it was analyzed using descriptive and regression analysis, which had been tested its validity and reliability trough pearson product moment. The result of this research proved in general the participants had good Pancasila personality development. Students as young generation should keep nationality personality in responding the science and technology challange, and hold on Pancasila as national principle so the development of science and technology can help national development